The foreclosure and the eviction - Gisbert Pomata, Marta (Razón y fe, 2018)
Aware of the serious situation that thousand of Spanish people are going through, insolvent and unable to pay their mortgages, Razón y Fe published an article on the December issue of 2011 supporting payment of debts due to mortgage default. We are addressing this issue again due to what we have been through in the past few months. In this article you will see from the point of view of legal practice the procedure needed in Spain for any foreclosure. You will also see the three royal decrees laws required due to the recent situation. Our aim reminds still the same: favoring a climate of dialogue so nobody feels evicted from their home.
Keywords: crisis; housing; mortgage; eviction; payment of debts; Royal Decrees; Law 27/2012